Effect of 6-Benzoyl-benzothiazol-2-one scaffold on the pharmacological profile of α-alkoxyphenylpropionic acid derived PPAR agonists. (1st January 2020) - Hurtevent, Aurélie; Le Naour, Morgan; Leclerc, Veronique; Carato, Pascal; Melnyk, Patricia; Hennuyer, Nathalie; Staels, Bart; Beucher-Gaudin, Monique; Caignard, Daniel-Henri; Dacquet, Catherine; Lebegue, Nicolas
Abstract: A series of nitrogen heterocycles containing α–ethoxyphenylpropionic acid derivatives were designed as dual PPARα/γ agonist ligands for the treatment of type 2 diabetes (T2D) and its complications. 6-Benzoyl-benzothiazol-2-one was the most tolerant of the tested heterocycles in which incorporation of O-methyl oxime ether and trifluoroethoxy group followed by enantiomeric resolution led to the ( S )-stereoisomer 44 b displaying the best in vitro pharmacological profile. Compound 44 b acted as a very potent full PPARγ agonist and a weak partial agonist on the PPARα receptor subtype. Compound 44 b showed high efficacy in an ob/ob mice model with significant decreases in serum triglyceride, glucose and insulin levels but mostly with limited body-weight gain and could be considered as a selective PPARγ modulator (SPPARγM).